2015
DOI: 10.1093/heapro/dav016
|View full text |Cite
|
Sign up to set email alerts
|

Researching health-related quality of life at a community level: results from a population survey conducted in Burgas, Bulgaria

Abstract: Researching health-related quality of life (HrQoL) at a community health promotion level is an approach to understand the health inequalities. The objective of this study is to measure the health of a representative sample by conducting a population survey in Burgas by using the EuroQoL EQ-5D-3L questionnaire, and further to assess the influence of socio-economic, demographic and behavioural factors on HrQoL. The relationship between HrQoL and social capital is analysed through a network-based approach. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
8
2
Order By: Relevance
“…Compared to previous research regarding SRH, a longer educational career (Kim, 2011), fewer symptoms (Jarbøl, 2017), better qualitative sleep customs (Darviri, 2011), deeper social capital (Vankova, 2016), moderate alcohol consumption (Badawi, 2012) and having medical insurance (Kim, 2011) were the same factors associated with better SRH. Regarding smoking, previous studies showed the opposite outcome.…”
Section: Discussioncontrasting
confidence: 50%
“…Compared to previous research regarding SRH, a longer educational career (Kim, 2011), fewer symptoms (Jarbøl, 2017), better qualitative sleep customs (Darviri, 2011), deeper social capital (Vankova, 2016), moderate alcohol consumption (Badawi, 2012) and having medical insurance (Kim, 2011) were the same factors associated with better SRH. Regarding smoking, previous studies showed the opposite outcome.…”
Section: Discussioncontrasting
confidence: 50%
“…Two of them were large European multi-country studies that involved more than one CEE country [45,46]. Overall 152 reports on country level results were obtained: Austria (n=11) [47][48][49][50][51][52][53][54][55][56][57], Bulgaria (n=6) [45,46,58,59,13], Czech Republic (n=18) [60,61,45,46,[62][63][64][65][66]20,[67][68][69][70][71][72][73][74], Hungary (n=47) [11,75,76,45,[77][78][79][80][81][82][83][84][85][86]…”
Section: Search Resultsmentioning
confidence: 99%
“…Among these, we found representative population norms from Hungary, Poland and Slovenia [11,136,149,115,164,180]. Further, local population norm is available for the city of Burgas in Bulgaria [59].…”
Section: Population Normsmentioning
confidence: 96%
“…The obtained results can be compared with other studies in Bulgaria. D. Vankova et al (2015) analyze the health-related quality of life (HrQoL) in a representative excerpt for the region of Burgas. Difficulties in at least one of the five dimensions are found it 548 (52.2%) of the respondents.…”
Section: Todorova M Et Almentioning
confidence: 99%
“…The health-related quality of life is a multi-dimensional concept, integrating aspects related to the physical, mental, emotional and social functioning. The main focus is on the consequences of the disease influencing the life standard and health well-being of the personality (4,5).…”
Section: Introductionmentioning
confidence: 99%